Long-term environmental enrichment is associated with better fornix microstructure in older adults - Klimecki, Olga M.; Liebscher, Maxie; Gaubert, Malo; Hayek, Dayana; Zarucha, Alexis; Dyrba, Martin; Bartels, Claudia; Buerger, Katharina; Butryn, Michaela; Dechent, Peter; Dobisch, Laura; Ewers, Michael; et al. (Frontiers in Aging Neuroscience, 2023)
Background: Sustained environmental enrichment (EE) through a variety of leisure activities may decrease the risk of developing Alzheimer’s disease. This cross-sectional cohort study investigated the association between long-term EE in young adulthood through middle life and microstructure of fibre tracts associated with the memory system in older adults. Methods: N=201 cognitively unimpaired participants (≥ 60 years of age) from the DZNE-Longitudinal Cognitive Impairment and Dementia Study (DELCODE) baseline cohort were included. Two groups of participants with higher (n=104) or lower (n=97) long-term EE were identified, using the self-reported frequency of diverse physical, intellectual and social leisure activities between the ages 13 to 65. White matter (WM) microstructure was measured by fractional anisotropy (FA) and mean diffusivity (MD) in the fornix, uncinate fasciculus, and parahippocampal cingulum using diffusion tensor imaging. Long-term EE groups (lower/higher) were compared with adjustment for potential confounders, such as education, crystallized intelligence and socio-economic status. Results: Reported participation in higher long-term EE was associated with greater fornix microstructure, as indicated by higher FA (standardized β=0.117, p=.033) and lower MD (β=-0.147, p=.015). Greater fornix microstructure was indirectly associated (FA: unstandardized B=0.619, p=.038; MD: B=-0.035, p=.026) with better memory function through higher long-term EE. No significant effects were found for the other WM tracts. Conclusion: Our findings suggest that sustained participation in a greater variety of leisure activities relates to preserved WM microstructure in the memory system in older adults. This could be facilitated by the multimodal stimulation associated with the engagement in a physically, intellectually and socially enriched lifestyle. Longitudinal studies will be needed to support this assumption.